Identità del soggetto e rapporto percettivo. L’interpretazione hegeliana del De anima di Aristotele - Bortolato, Filippo (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: This paper deals with the interpretation that Hegel gave of De anima and the consequences this reading brings to the Hegelian anthropology. The charge against empiricist epistemology and its description of the soul puts forward the problem about the sensation, which Empiricism has characterized as passive determination made by the causal action of the things on the subject. In opposition to this account of the sensation, Hegel reexamined the Aristotelian theory of sensibility in its presuppositions: the ideas of compensative alteration and identity of potential conditions which depend on the concept of life as entelechy. He accounted for such concepts in his own fashion and argued that our sensation already has an unitary relation with the subject, and by means of it the perception is reduced in an unitary structure.